2010
DOI: 10.1017/s1461145710000490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunctive treatment with aripiprazole on body weight and clinical efficacy in schizophrenia patients treated with clozapine: a randomized, double-blind, placebo-controlled trial

Abstract: Clozapine is associated with significant weight gain and metabolic disturbances. This multicentre, randomized study comprised a double-blind, placebo-controlled treatment phase of 16 wk, and an open-label extension phase of 12 wk. Outpatients who met DSM-IV-TR criteria for schizophrenia, who were not optimally controlled while on stable dosage of clozapine for > or =3 months and had experienced weight gain of > or =2.5 kg while taking clozapine, were randomized (n=207) to aripiprazole at 5-15 mg/d or placebo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(115 citation statements)
references
References 26 publications
6
100
0
9
Order By: Relevance
“…Studies in AP-naïve individuals show that patients treated with low metabolic liability APs experience significant weight gain (Correll et al 2009;Perez-Iglesias et al 2008;Zipursky et al 2005) and, in general, experience a three-to fourfold larger magnitude of antipsychotic-related weight gain compared to chronically ill patients (Alvarez-Jimenez et al 2008). In contrast, but in keeping with the presented rodent data, chronically treated patients have been reported to lose weight with ARI when added to CLO Fleischhacker et al 2010;Henderson et al 2006). It is unclear why this discrepancy exists between weight effects in individuals with little prior AP exposure and chronically ill patients; it is possible that different mechanisms underlie the more acute metabolic changes versus chronic weight gain (where additional factors related to illness and lifestyle may also come into play).…”
Section: Discussion/conclusionsupporting
confidence: 68%
“…Studies in AP-naïve individuals show that patients treated with low metabolic liability APs experience significant weight gain (Correll et al 2009;Perez-Iglesias et al 2008;Zipursky et al 2005) and, in general, experience a three-to fourfold larger magnitude of antipsychotic-related weight gain compared to chronically ill patients (Alvarez-Jimenez et al 2008). In contrast, but in keeping with the presented rodent data, chronically treated patients have been reported to lose weight with ARI when added to CLO Fleischhacker et al 2010;Henderson et al 2006). It is unclear why this discrepancy exists between weight effects in individuals with little prior AP exposure and chronically ill patients; it is possible that different mechanisms underlie the more acute metabolic changes versus chronic weight gain (where additional factors related to illness and lifestyle may also come into play).…”
Section: Discussion/conclusionsupporting
confidence: 68%
“…The authors described significant reductions in both weight (−2.70 kg) and Body Mass Index (BMI) without worsening of psychotic symptoms. Significant decreases in weight (−2.15 kg) were also seen in a 2010 16-week trial of 5-15 mg adjunctive aripiprazole in clozapine-treated patients [31]. Aripiprazole Non-pharmacological interventions may therefore be beneficial in decreasing weight gain in clozapine-treated patients with schizophrenia, but, as with other SGAs, the side effect profile should be considered in balance with the potential benefits.…”
Section: Antipsychotic Drugsmentioning
confidence: 99%
“…Correll et al (2007) reported that the prescription of multiple antipsychotics was associated with a significant increase in the incidence of metabolic syndrome (50%) compared with antipsychotic monotherapy (34%). Conversely, the combination of clozapine and aripiprazole has been found to reduce triglyceride levels, LDL cholesterol, BMI and waist circumference, as well as negative symptoms, in patients with schizophrenia and metabolic syndrome (Fleischhacker 2010). This is probably because aripiprazole is a partial dopamine agonist that stimulates extracerebral presynaptic D 2 receptors, which decreases sympathetic tone and anabolic effects, thereby reducing the risk of metabolic syndrome.…”
Section: Antipsychoticinduced Weight Gainmentioning
confidence: 99%